Indian Monsoons and Himalayan Water Conservation - Dewan, M.L (Journal of Soil and Water Conservation, 2022)
Every year, during the monsoons, 320 million, hectare metres of water descends on the Indian sub-continent. If all this rainfall were collected, it would form a one-metre thick sheet of water over our landmass. It is the largest volume of its kind that falls anywhere in the world. Yet, we have become a nation of water famine and drought, says Dr. Pisharoty. Because we are not practising the method of efficiency using all the rainwater that falls on the ground. We are depending too much on modern technology, like dams. Perhaps, the population was sufficiently low. earlier. So that special methods were not needed over major parts of the country to collect water. Industrial needs for water too were not there a hundred years ago. However, in areas where rainfall had been low, and year to year vagaries high, people developed in- novative methods which have now by and large been forgotten. These methods included collecting and harvesting water from the roofs of individual houses and from farms and wastelands, etc. There is evidence that such methods were extensively used in regions of low-rainfall like Kutch, parts of Saurashtra, etc. We had the extensive use of the tank- culture in the southern states from the earliest days. That was also a type of harvesting water economically.